Defining the roles and responsibilities of the kidney transplant medical director: A necessary step for future training, mentoring, and professional development. Issue 4 (4th November 2020) - C. Wiseman, Alexander; Akalin, Enver; M. Dadhania, Darshana; DeMattos, Angelo; Doshi, Mona; Friedewald, John; Klein, Christina; Leca, Nicolae; Nicoll, Kim; Pesavento, Todd; Preczewski, Luke; Samaniego, Millie; et al.
Abstract : The management of a kidney transplant program has evolved significantly in the last decades to become a highly specialized, multidisciplinary standard of care for end‐stage kidney disease. Transplant center job descriptions have similarly morphed with increasing responsibilities to address a more complex patient mix, increasing medical and surgical therapeutic options, and increasing regulatory burden in the face of an ever‐increasing organ shortage. Within this evolution, the role of the Kidney Transplant Medical Director (KTMD) has expanded beyond the basic requirements described in the United Network for Organ Sharing bylaws. Without a clear job description, transplant nephrology trainees may be inadequately trained and practicing transplant nephrologists may face opaque expectations for the roles and responsibilities of Medical Director. To address this gap and clarify the key areas in which the KTMD interfaces with the kidney transplant program, American Society of Transplantation (AST) formed a Task Force of 14 AST KTMDs to review and define the role of the KTMD in key aspects of administrative, regulatory, budgetary, and educational oversight of a kidney transplant program. Abstract : This report from the American Society of Transplantation Task Force describes the multifaceted position of kidney transplant medical director, which has evolved over the past decades with an increasing mandate for subspecialization, more complex medical management, and recognition of financial value to transplant programs.